2009
DOI: 10.1002/icd.636
|View full text |Cite
|
Sign up to set email alerts
|

Sleep arrangements and night waking at 6 and 12 months in relation to infants' stress‐induced cortisol responses

Abstract: The objective of this short-term longitudinal study was to examine the concurrent and prospective associations of infants' sleep arrangements and night waking with cortisol responses to an inoculation at 6 and 12 months, controlling for several key covariates. To our knowledge, this was the first study to concurrently and prospectively link proximity in sleep arrangements and night waking to physiological stress reactivity. A sample of 92 mother-infant dyads participated in the study when the infants were 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Although few studies addressed infant hormonal factors, results suggested a trend for an association between a regulation of the HPA axis and less night wakings (Lucas-Thompson et al, 2009) and more sleep during the night (Lucas-Thompson et al, 2009). Results from a recent study were controversial, however, this study was conducted with infants with colic (Brand et al, 2011), and colic were shown to be associated with infant sleep-wake behaviour in previous research (Kirjavainen et al, 2001;White et al, 2000).…”
Section: Factors Positively and Negatively Associated With Sleep-wakementioning
confidence: 79%
“…Although few studies addressed infant hormonal factors, results suggested a trend for an association between a regulation of the HPA axis and less night wakings (Lucas-Thompson et al, 2009) and more sleep during the night (Lucas-Thompson et al, 2009). Results from a recent study were controversial, however, this study was conducted with infants with colic (Brand et al, 2011), and colic were shown to be associated with infant sleep-wake behaviour in previous research (Kirjavainen et al, 2001;White et al, 2000).…”
Section: Factors Positively and Negatively Associated With Sleep-wakementioning
confidence: 79%
“…After six-week data collection, the sleep group received the infant safety information and the safety group received the infant sleep information. We provided the safety group with infant sleep information because the literature indicates infants’ BSPs have negative outcomes for parents [ 10 – 12 ] and infants [ 4 ] and we regarded it as unethical to withhold a potentially useful intervention in the absence of any standard accessible treatment for infant BSP.…”
Section: Methodsmentioning
confidence: 99%
“…Predominant problems identified by parents are infants’ difficulties in falling asleep and staying asleep [ 2 ], which create fragmented sleep and/or short sleep duration. Adequate sleep duration is associated with increased infant adaptability and rhythmicity [ 3 ], while night waking with crying has been associated with greater stress reactivity, for example, during inoculations [ 4 ]. Young children’s BSPs have been linked to hyperactivity, and cognitive, emotional, and behavioral difficulties, after controlling for maternal depressive symptoms [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…But other research indicates there are no lasting negative effects of the crying associated with extinction 42 and early life experiences, such as co-sleeping, have also been shown to cause poorer stress responses in different situations. 48,50 Often these conflicting findings are not presented or are poorly explained in the media and parenting networks, and the information presented in many parenting networks share a similar ideological stance and wish to show evidence to support it. Parents can be left with the impression these findings are definitive and that extinction is or is not harmful.…”
Section: Fear Of Repercussionsmentioning
confidence: 99%